2013
DOI: 10.1371/journal.pone.0061863
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation in Motor Sequence Learning Is Related to the Level of Native Cortical Excitability

Abstract: Cortical excitability may be subject to changes through training and learning. Motor training can increase cortical excitability in motor cortex, and facilitation of motor cortical excitability has been shown to be positively correlated with improvements in performance in simple motor tasks. Thus cortical excitability may tentatively be considered as a marker of learning and use-dependent plasticity. Previous studies focused on changes in cortical excitability brought about by learning processes, however, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
2
14
1
Order By: Relevance
“…The present findings complement the results of a previous study (Lissek et al, 2013 ) in which we demonstrated in healthy participants that CE remained unchanged after learning and training of an identical motor sequence task. Moreover, the inverse relation of CE and learning performance found in the tiapride group corresponds to the findings of a study using the DA-agonist cabergoline, which for a simple motor practice task of thumb movements showed an increase in practice-dependent plasticity combined with a decrease in CE (Meintzschel and Ziemann, 2006 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present findings complement the results of a previous study (Lissek et al, 2013 ) in which we demonstrated in healthy participants that CE remained unchanged after learning and training of an identical motor sequence task. Moreover, the inverse relation of CE and learning performance found in the tiapride group corresponds to the findings of a study using the DA-agonist cabergoline, which for a simple motor practice task of thumb movements showed an increase in practice-dependent plasticity combined with a decrease in CE (Meintzschel and Ziemann, 2006 ).…”
Section: Discussionsupporting
confidence: 92%
“…Motor training can increase motor CE (Abbruzzese et al, 1996 ; Koeneke et al, 2006 ; Cirillo et al, 2010 , 2011 ), while increased motor CE positively correlates with performance improvements in simple motor tasks (Muellbacher et al, 2001 ; Ziemann et al, 2001 ). However, a recent study using a complex motor task found no increase of CE after task training and performance (Lissek et al, 2013 ), which is in line with two previous studies that used less complex tasks (Ziemann et al, 2001 ; Smyth et al, 2010 ). Therefore, it is debatable whether changes in CE in motor cortex can be considered indicators of motor learning and use-dependent plasticity.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…To address this question, we used the pigeon as an animal model and the nucleus dorsolateralis anterior thalami (DLA) as the target brain area. The pigeon is a common animal model for behavioral and neurobiological studies of time-dependent cognitive tasks, such as interval timing ( Kalenscher et al, 2006 ), sequence learning ( Helduser et al, 2013 ; Lissek et al, 2013 ), and delayed matching-to-sample ( Browning et al, 2011 ). Furthermore, to achieve foraging and safe flight successfully in diverse environments, birds have developed a complex visual system that is superior to that of most vertebrates ( Shimizu and Watanabe, 2012 ; Wylie et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%